THE EFFECT OF SHARIA MARKETING THROUGH SOCIAL MEDIA ON PURCHASING DECISIONS GARDENIA BOGOR HOUSING - Ariani, Fika Ghilda; Herawati, Ermi; Al Farisi, Muhammad Salman (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to measure and analyze the effect of sharia marketing and social media promotion on the purchasing decisions of consumers of Gardenia Bogor Housing. This study uses a quantitative descriptive approach. The population in this study is the Muslim community selected based on the radius of the target location of advertisements on social media used by Gardenia Bogor Housing, with a total of 100 respondents. The sampling technique used is purposive sampling. The data was analyzed using the Statistical Package for the Social Sciences (SPSS) Statistics Data Version 22. The results of this study indicate that the variables of sharia marketing and social media promotion have a significant positive effect on purchasing decisions.